New museographic frontiers. Immateriality and multimediality of the narrative museum - Giuseppe Di Benedetto (Agathón)
The contribution explores, also through the reading of some case studies, the constitutive and connotative aspects of what can be defined as the new ‘frontier of museography’. A ‘frontier’ recognisable in the definition of museum structured according to the concept of ‘integrated installation’ which is mainly based on the combination of advanced technological equipment, art and interactivity of museographic content dissemination systems. In these last years several museum experiences have been developed, characterised by investigations on the new technological languages, but not neglecting the fundamental elaboration of aims and contents of the same exhibition projects characterised by the relation material/immaterial. This is an articulated path that crosses the boundaries of various disciplines such as theatre, cinema and visual art.